Mortality, life expectancy, and causes of death of persons with hemophilia in the Netherlands 2001–2018 - Hassan, Shermarke (J Thromb Haemost, 2020)
BACKGROUND: Treatment of patients with hemophilia has advanced over the past decades, but it is unknown whether this has resulted in a normal life expectancy in the Netherlands. OBJECTIVE: This observational cohort study aimed to assess all‐cause and cause‐specific mortality in patients with hemophilia in the Netherlands between 2001 and 2018 and to compare mortality and life expectancy with previous survival assessments from 1973 onward. PATIENTS/METHODS: All 1066 patients with hemophilia who participated in a nationwide survey in 2001 were followed until July 2018. RESULTS: Information on 1031 individuals (97%) was available, of whom 142 (14%) deceased during follow‐up. Compared with the general Dutch male population, mortality of patients with hemophilia was still increased (standardized mortality ratio: 1.4, 95% confidence interval: 1.2–1.7). Intracranial bleeding and malignancies were the most common causes of death. Estimated median life expectancy of patients with hemophilia was 77 years, 6 years lower than the median life expectancy of the general Dutch male population (83 years). Over the past 45 years, death rates of patients with hemophilia have consistently decreased, approaching the survival experience of the general population. Over the past decades, mortality due to human immunodeficiency virus and hepatitis C virus infections has decreased, death due to intracranial hemorrhages has increased, and death due to ischemic heart disease has remained consistently low over time. CONCLUSIONS: Survival in patients with hemophilia in the Netherlands has improved over time but is still lower than that of the general population.